2018
DOI: 10.3390/app8040595
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Design and Model Assessment of a Supercritical CO2 Compressor

Abstract: Abstract:The compressor is a key component in the supercritical carbon dioxide (SCO 2 ) Brayton cycle. In this paper, the authors designed a series of supercritical CO 2 compressors with different parameters. These compressors are designed for 100 MWe, 10 MWe and 1 MWe scale power systems, respectively. For the 100 MWe SCO 2 Brayton cycle, an axial compressor has been designed by the Smith chart to test whether an axial compressor is suitable for the SCO 2 Brayton cycle. Using a specific speed and a specific d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 31 publications
0
6
0
1
Order By: Relevance
“…Данный подход к определению границы успешно использован в работе [4], однако, в работе [5] отмечается, что данный критерий имеет существенные ограничения по режиму работы компрессора.…”
Section: существующие подходы к определению гурunclassified
“…Данный подход к определению границы успешно использован в работе [4], однако, в работе [5] отмечается, что данный критерий имеет существенные ограничения по режиму работы компрессора.…”
Section: существующие подходы к определению гурunclassified
“…As one of the compression devices, the centrifugal compressor has the advantages of high single-stage pressure ratio, ow stability, compactness, cheapness, etc. Our previous research showed that the centrifugal compressor is the most suitable type of compression component in a 1-100 MWe supercritical CO 2 Brayton cycle power generation system [12,13]. A literature survey reported by [14,15] revealed that most of the existing supercritical CO 2 experimental rigs adopted the centrifugal type as the compression component.…”
Section: Introductionmentioning
confidence: 99%
“…The above analysis shows that the impeller inlet aerodynamic and geometrical parameters are coupled and interacted. In recent years, some preliminary design methods for SCO 2 compressors were developed by integrating the real gas model and the mean-line methods of air compressors [18,20]. However, those methods usually paid more attention to explore the impeller outlet parameters of SCO 2 compressors [19,21], and they cannot well cope with the interactions among impeller inlet parameters.…”
Section: Introductionmentioning
confidence: 99%